2015
DOI: 10.1364/optica.2.000076
|View full text |Cite
|
Sign up to set email alerts
|

Low-power, chip-based stimulated Brillouin scattering microwave photonic filter with ultrahigh selectivity

Abstract: Highly selective and reconfigurable microwave filters are of great importance in radiofrequency signal processing. Microwave photonic (MWP) filters are of particular interest, as they offer flexible reconfiguration and an order of magnitude higher frequency tuning range than electronic filters. However, all MWP filters to date have been limited by trade-offs between key parameters such as tuning range, resolution, and suppression. This problem is exacerbated in the case of integrated MWP filters, blocking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
213
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 334 publications
(223 citation statements)
references
References 68 publications
1
213
0
1
Order By: Relevance
“…With careful design, such Brillouin nonlinearities overtake all other nonlinear processes in silicon [6,7]; these same Brillouin interactions are remarkably tailorable, permitting a range of hybrid photonic-phononic signal processing operations that have no analog in all-optical signal processing [8][9][10][11][12]. Using this physics, the rapidly growing field of silicon-based Brillouin-photonics has produced new frequency agile RFphotonic notch filters [8,10,13,14] and multi-pole bandpass filters [12] as the basis for radio-frequency photonic (RF-photonic) signal processing. Beyond these specific examples, the potential impact of such Brillouin interactions is immense; frequency combs [13,15,16], ultra-low phasenoise lasers [17][18][19], sensors [9,12,20], optical isolation [21][22][23][24], and an array of signal processing technologies [8,[12][13][14][25][26][27]] may be possible in silicon with further progress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With careful design, such Brillouin nonlinearities overtake all other nonlinear processes in silicon [6,7]; these same Brillouin interactions are remarkably tailorable, permitting a range of hybrid photonic-phononic signal processing operations that have no analog in all-optical signal processing [8][9][10][11][12]. Using this physics, the rapidly growing field of silicon-based Brillouin-photonics has produced new frequency agile RFphotonic notch filters [8,10,13,14] and multi-pole bandpass filters [12] as the basis for radio-frequency photonic (RF-photonic) signal processing. Beyond these specific examples, the potential impact of such Brillouin interactions is immense; frequency combs [13,15,16], ultra-low phasenoise lasers [17][18][19], sensors [9,12,20], optical isolation [21][22][23][24], and an array of signal processing technologies [8,[12][13][14][25][26][27]] may be possible in silicon with further progress.…”
mentioning
confidence: 99%
“…Using this physics, the rapidly growing field of silicon-based Brillouin-photonics has produced new frequency agile RFphotonic notch filters [8,10,13,14] and multi-pole bandpass filters [12] as the basis for radio-frequency photonic (RF-photonic) signal processing. Beyond these specific examples, the potential impact of such Brillouin interactions is immense; frequency combs [13,15,16], ultra-low phasenoise lasers [17][18][19], sensors [9,12,20], optical isolation [21][22][23][24], and an array of signal processing technologies [8,[12][13][14][25][26][27]] may be possible in silicon with further progress.However, strong Brillouin amplification-essential to many new Brillouin-based technologies-has yet to be realized in silicon photonics. Despite the creation of strong Brillouin nonlinearities in a range of new structures [6,7], nonlinear losses and free carrier effects have stifled attempts to demonstrate net optical amplification.…”
mentioning
confidence: 99%
“…Some salient works demonstrated remarkable filter features that outrun state-of-the-art allelectronics implementations, such as terahertz bandwidth [40], multi-octave tuning [41], nanosecond switching speed [42], microwatt control [43], and power extinction exceeding 60 dB [44]. Recent work of ours proposed and experimentally demonstrated a full-integration-ready approach of such filters with DSP-like flexibility by means of introducing software-defined circuit programmability into the processing core chips [45].…”
Section: System Architecturementioning
confidence: 97%
“…Utilizing the SBS effect in a 6.5-cm-long As2S3 waveguide, Morrison et al [109], Byrnes et al [110], and Choudhary et al [111] demonstrated respectively an RF bandstop filter and narrow bandpass filter with tunable bandwidth and center frequency as shown in Figure 26B. In a later work Marpaung et al [44], associated such SBS effect with a particular modulation spectrum comprising uneven sidebands and therewith demonstrated a highly selective RF notch filter with a very deep notch of 60 dB and a large frequency tuning range of 30 GHz as shown in Figure 27A. Recently, aimed to facilitate the integration of the SBS effect with other processing functions on a chip, Casas-Bedoya et al [112] demonstrated a similar RF filter function using a silicon waveguide that has its substrate particularly treated to provide high SBS efficiency as shown in Figure 27B.…”
Section: Various Filter Implementationsmentioning
confidence: 98%
See 1 more Smart Citation